2013
DOI: 10.4172/2155-9597.1000176
|View full text |Cite
|
Sign up to set email alerts
|

Co-Endemicity of Plasmodium falciparum and HIV-Infections in Treated Patients is Uncorrelated in Benin City, Nigeria

Abstract: The Human immunodeficiency virus (HIV) and malaria are two of the world's most formidable pathogens. Coinfection has been shown to amplify the effects of both diseases with HIV infection enhancing the severity of malaria. Previous work in our laboratory has shown that individuals infected with malaria and HIV who are taking anti-retrovirals have the Plasmodium parasite in their bloodstream suggesting that the lack of anti-malarials in their drug regimen resulted in Plasmodium infection. In this study, we set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
1
2
1
Order By: Relevance
“…Analysis of sex-related prevalence of malaria among the HIV-infected patients in this study revealed that more men than women were co-infected. This finding corresponds with the findings of Akinbo et al 9 and Wariso, 18 but contradicts the report of Saracino et al 19 who found higher co-infection rate in women. The finding from this study is most likely due to men having more exposure to the parasite as a result of day-to-day activities which could extend till late in the night.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Analysis of sex-related prevalence of malaria among the HIV-infected patients in this study revealed that more men than women were co-infected. This finding corresponds with the findings of Akinbo et al 9 and Wariso, 18 but contradicts the report of Saracino et al 19 who found higher co-infection rate in women. The finding from this study is most likely due to men having more exposure to the parasite as a result of day-to-day activities which could extend till late in the night.…”
Section: Discussionsupporting
confidence: 80%
“…The prevalence of malaria in patients attending 3 major hospitals in Abuja, FCT, was observed to be 33.8% (142 of 420). The co-infection rate from this study is extremely high (33.8%), compared with the 2.9% obtained in Lagos 6 ; the 7.8% reported in Kogi 10 ; the 2.11% and 9.78% found in Benin City, Nigeria 8,9 ; the 18.81% reported by Chinedum et al 13 ; and the 4% observed in Uganda. 17 A higher co-infection rate (43.96%) than that obtained from this study has however been found in South-Eastern Nigeria by Ukibe et al 12 The high rate of malaria co-infection seen in this study could be indicative of the increased exposure of HIV-infected patients to the parasite.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…A High level of HIV-malaria co-infection has been documented during the post-ART era. Akinbo et al, in his research study, reported HIV-malaria co-infection prevalence of 9.8% and 7.8%, respectively (Akinbo Omoregie et al, 2013;Akinbo, Anate et al, 2016). Similarly, the relatively higher prevalence was reported among participants on ART.…”
Section: Introductionmentioning
confidence: 85%